Plant antigens cross-react with rat polyclonal antibodies against KLH-conjugated peptides - Oulehlová, Denisa; Hála, Michal; Potocký, Martin; Zárský, Viktor; Cvrcková, Fatima (Cell biology international, 2009)
Keyhole limpet hemocyanin (KLH)-conjugated peptides are routinely used to raise polyclonal antibodies for biochemical or immunolocalization studies. Rats are suitable for producing antisera against plant antigens as they often lack non-specific response towards plant materials. We attempted to obtain rat antisera against peptides derived from several plant proteins. However, most antisera recognized the same background KLH-related plant antigen (KRAP) in Arabidopsis and tobacco. We characterized KRAP with respect to size and cellular localization and examined possible antigen-specific reasons for the failure of most immunizations. We also found no reports of successful use of rat anti-KLH-peptide antibodies in plant studies. We thus believe that the rat-KLH:peptide system is poorly suited for production of antibodies, especially against plant antigens, and should be used with caution, if at all.
Keywords: Hemocyanins; sekvence aminokyselin; Cross Reactions; Peptides; peptidy; krysa rodu Rattus; hemokyanin; molekulární sekvence - údaje; protilátky; Amino Acid Sequence; Antibodies; Animals; Molecular Sequence Data; Antigens, Plant; zkřížené reakce; antigeny rostlinné; zvířata; Rats